Ecological Metaphors in the Lontar manuscript of the Megantaka folklore: An ecolinguistics analysis - Assiddiq, Muhammad Azwar; Mustari, Sri Hariati; Pilu, Reski; Mustakim, Mustakim (Studies in English Language and Education, 2025)
This study investigates the ecological metaphors used in the lontar manuscript of the Megantaka folklore of the Sasak tribe in Indonesia. Using an ecolinguistic approach and referring to Halleys ecological metaphor categories, the data were collected from the Lontar manuscript and analysed using the Metaphor Identification Method (MIP). The findings revealed that the metaphors belong to several categories: 1) the being category used in Tembang Sinom and Tembang Dandang, 2) the cosmos category appearing in Tembang Durma, Tembang Pangkur, and Tembang Dandang, 3) the energy category in Tembang Asmaradana, Tembang Durma, and Tembang Pangkur, 4) the substance category in Tembang Durma, 5) the terrestrial category in Tembang Durma, Tembang Pangkur, and Tembang Dandang, 6) the object category in Tembang Sinom, Tembang Asmaradana, Tembang Pangkur, and Tembang Dandang, 7) the living category in Tembang Durma, Tembang Pangkur, and Tembang Dandang, and 8) the animate category in Tembang Durma, Tembang Pangkur, and Tembang Dandang. This study is essential for preserving local wisdom, providing an overview of social and cultural life in the past, and serving as material for community reflection in strengthening the national character. This study reflects the ecological conditions of language users and provides insights into the social and cultural lives of the Sasak people.